THE EFFECTS OF RILL EROSION ON UNPAVED FOREST ROAD - Varol, Tuğrul; Ertuğrul, Mertol; Özel, Halil Barış; Emir, T.; Cetin, M. (ALOKI Ltd, 2019)
This research aims to investigate the degree of rill erosion and its relationship with the factors effective on rill volume on unpaved forest roads in Bartin Province in Turkey. For this purpose, measurements were made at 380 sample locations on different regions of the forest roads in Ant and Hasankadi sub-districts. The measurements were performed on 4 years old unpaved forest roads. Among the road surface (RS), road cut (RC), sidecast fill (SCF) and skid trail (ST) road sections, RS and ST ranked as the first two sections with the highest segment length. Segment length is characterized as the most effective field factor on erosion, which further increased the rill volume by the combined effect of increasing slope, in this research. According to the stepwise (forward-backward) regression analysis results, inclusion of both segment length and slope parameters in the RS, SCF and RC equations supports this finding. The correlation of all road sections (RS, SCF, RC, ST) with the segment length are 0.84, 0.63, 0.75 and 0.83, respectively, and the correlation with the slope are 0.55, 0.73, 0.57 and 0.64, respectively. As a result of the slope based categorization of the relationship between segment lengths and rill volume for the road sections, R-2 values were found to increase up to 0.88 for RS, 0.78 for SCF, 0,94 for RC and 0.88 for ST. The rill volume at short and steep roads can be lower than the rill volume at long and low-slope roads. Therefore, we calculated the rill volumes per unit road segment area. As a result of application of equations based on shear stress and stream power sediment transport capacity theory, RMSE values with very low mean error were obtained. In further related studies, drainage areas in addition to segment lengths and slope should also be taken into account to determine the positive and negative effects in evaluation of rill erosion amounts. Also, similar studies should be performed on other basins having a larger number of unpaved forest roads as a means to extend the applicability of the obtained findings.
Keywords: Road Erosion; Sediment Sources; Agronomy and Crop Science; Soil Loss; Hydrological Constituents; Unpaved Road